Pengaruh Warna Umpan terhadap Hasil Tangkapan Ikan Cakalang (Katsuwonus pelamis) pada Alat Tangkap Pancing Ulur di Perairan Prigi, Kabupaten Trenggalek - Gilang Anugrah Kusma Fitranda; Exist Saraswati; Yusrudin Yusrudin (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Handline fishing is a simple fishing gear widely used by fishermen in the waters of Prigi, Trenggalek Regency. One of the target fish species for this fishing gear is skipjack tuna (Katsuwonus pelamis). This study aims to determine the effect of bait color on the catch of skipjack tuna using handline fishing in the waters of Prigi. The research method used was experimental fishing with a Randomized Block Design (RBD), testing three different bait colors: red, blue, and white. The study was conducted over nine fishing trips, and the catch results were analyzed using variance analysis (ANOVA) and the Least Significant Difference (LSD) test. The results showed that the red bait yielded the highest catch with 314 fish, followed by blue with 251 fish, and white with 216 fish. The variance analysis indicated a significant difference in the effect of bait color on skipjack tuna catch. Thus, it can be concluded that using red-colored bait is more effective in increasing skipjack tuna catches compared to blue and white bait.